Disabled veterans in history - Gerber, David A. (Corporealities, 2012)
Explores the long-neglected history of those who have sustained lasting injuries or chronic illnesses while serving in uniform. The contributors to this volume cover an impressive range of countries in Europe and North America as well as a wide sweep of chronology from the Ancient World to the present.